Secure performance analysis of WCDMA systems over correlated Nakagami fading channels - Guangqiu LI; Zhanwan WANG; Tingjie REN; Shuaishuai LIU (Dianxin kexue)
In order to evaluate the security performance of wideband code division multiple access (WCDMA) over multiple-input and multiple-output fading channels,a time-saving and efficient solution is theoretical analysis.The exact analytical expressions of the non-zero security capacity probability and the security outage probability of WCDMA systems using space-time block codes and 2D Rake receivers (2D-Rake) on the relevant Nakagami fading channels was deduced.Using the above expressions,the effects of parameters such as the number of transmit and receive antennas,antenna correlation coefficient,Nakagami fading coefficient,and average path attenuation coefficient on the security performance of the WCDMA system could be quickly evaluated.The numerical calculation was in good agreement with the simulation results,which proved the correctness of the above theoretical analysis.The analytical expression of the asymptotic safety outage probability of WCDMA system was deduced.The results show that the security diversity gain of WCDMA system is the sum of the diversity gains on the separable paths of the main channel,and has nothing to do with the eavesdropping channel; the same for the constant multipath intensity profile The Nakagami fading channel is distributed,and the security diversity gain of the WCDMA system is the product of the number of received and transmitted antennas of the primary channel,the number of multipaths,and the Nakagami fading coefficient.